Genetic and Clinical Characterization of Patients with Maturity-Onset of Diabetes of the Young (MODY): Identification of Novel Variations - GÜNEY, AHMET İLTER; POLAT, HAMZA; ELBASAN, ONUR; ÜSTAY, ÖZLEM; APAYDIN, TUĞÇE (AVES, 2021)
Background: Maturity-onset diabetes of the young (MODY) is a rare monogenic type of diabetes, and accounts for 2-5% of all diabetes cases. An early age of onset, a family history supporting autosomal-dominant inheritance, insulin resistance, and the absence of autoimmunity are the major characteristics of MODY. However, genetic testing is crucial for diagnosis. Aims: To investigate the 7 MODY-related genes and clinical findings of patients with a preliminary clinical diagnosis of MODY. Study Design: Retrospective cross-sectional study. Methods: In this study, 7 genes (KCNJ11, ABCC8, INS, GCK, HNF4A, HNF1A, and HNF1B) related to MODY were screened via targeted sequencing in 182 cases with a confirmed pre-diagnosis of MODY. The clinical characteristics of the patients were evaluated retrospectively. Results: A total of 182 patients, 48% of whom were women, between the ages of 18-62 were included in the study. In 30 cases (16.4%), 28 different pathogenic variations were found, of which 20 were previously reported and 8 were novel variations segregated by disease within the family. Pathogenic variations were detected in the following genes in order of mutation frequency; GCK, HNF1A, ABCC8, HNF4A, HNF1B and KCNJ11. Interestingly, six of the 30 cases (20%) carried a pathogenic variation in the ABCC8 gene. No mutation was detected in the INS gene. A family history of vertically transmitted diabetes and elevated HbA1C at the time of diagnosis were found in 20 (66%) and 16 (52%) cases, respectively. Conclusion: In this series, 28 different pathogenic variations are identified, 8 of which are novel. The rate of pathogenic variation in the ABCC8 gene is unexpectedly high. Two-thirds of cases have a family history of vertically transmitted diabetes.
Keywords: GLUCOKINASE